Pengaruh Pemberian Jamu Temulawak (Curcuma Zanthorrhiza L) Terhadap Penurunan Nyeri Menstruasi Pada Remaja Putri di SMAN 1 Porehu Kabupaten Kolaka Utara - Mustari, Rohani; Elis, Andi; Maryam, Andi; Zain, Siti Nur Hidayah binti Mohd (Lembaga Publikasi Ilmiah Nusantara, 2024)
Temulawak herbal medicine is an alternative intervention in reducing the level of menstrual pain. Temulawak contains chemical compounds that have physiological activity. The curcumin content is also known as an anti-tumor, antioxidant, and pain reducer. The research aims to determine the effect of administering ginger herbal medicine (Curcuma zanthorrhiza L) on reducing menstrual pain in adolescent girls at SMAN 1 Porehu, North Kolaka Regency. The type of research used was quasi-experimental using a one group pretest-posttest research design. The sample in this study was all 27 young women who experienced pain during menstruation. The research results showed that the scale of menstrual pain before administering ginger herbal medicine (Curcuma zanthorrhiza L) reduced menstrual pain in young women at SMAN 1 Porehu, North Kolaka district in the mild pain category was 1 (3.7%), the moderate pain category was 13 (48%). .1%) and the severe pain scale category was 13 (48.1%). However, after administering ginger herbal medicine (Curcuma zanthorrhiza L) the reduction in menstrual pain in adolescent girls at SMAN 1 Porehu, North Kolaka district experienced changes where menstrual pain in the painless category was 15 (55.5%), and in the mild pain category was 12 ( 44.4%),. The conclusion is that there is an effect of giving ginger herbal medicine (Curcuma zanthorrhiza L) on reducing menstrual pain in adolescent girls at SMAN 1 Porehu, North Kolaka Regency (p value of 0.000 < α 0.05).